A rapid method to increase transparency and efficiency in web-based searches. Issue 1 (December 2017) - Haddaway, Neal; Collins, Alexandra; Coughlin, Deborah; Kirk, Stuart
Abstract Background Many online search facilities allow searching for academic literature. The majority are bibliographic databases that catalogue published research in an iterative, semi-automated manner, e.g. Web of Science Core Collections, which indexes articles published in selected journals. Other resources, such as Google Scholar, identify academic articles by using search engines that crawl the internet for potentially relevant information. Often, systematic reviewers wish to document their searches for transparency or later screening. Indeed, such transparency is a cornerstone of systematic review methodology. Whilst bibliographic databases typically allow users to extract search results as citations in bulk, several other key resources, such as Google Scholar and organisation websites, do not allow this: citations must be extracted individually, which is often prohibitively time consuming. Methods Here, we describe novel methods for downloading results from searches of websites and web-based search engines into comprehensive databases as citations using free-to-use software. Citations from web-based search engines can then be integrated into review procedures along with those from traditional online bibliographic databases. Results and conclusions These methods substantially increase transparency and repeatability when searching online resources. They may also significantly reduce resource requirements for such searches and therefore represent a significant increase in efficiency.